An etiological analysis of proptosis - Teja, Nithin; Reddy, Manmitha; Vanama, Alekhya (International Journal of Research in Medical Sciences, 2017)
Background: The main objective of the study was to analyse the various causes for proptosis. Methods: A prospective analysis of 54 cases of proptosis. Detailed ocular and systemic history, examination and relevant investigations were done in necessary cases. Also other related specialties opinion obtained whenever indicated for diagnosis and treatment. Results: Out of 54 cases, 26 were axial and 28 were eccentric, 38 were unilateral, 16 were bilateral. Etiology of proptosis due to inflammation 20 cases, infectious 14 cases, neoplastic 10 cases, vascular 4 cases, traumatic 4 cases, others 2 cases. Conclusions: Thyroid eye disease is the single most common cause of proptosis in this study. Among neoplastic cases primary tumours were more common than secondary tumours in the orbit in this study. Orbital X-ray, B scan, CT scan and MRI were helpful in the diagnosis, treatment and follow up.